Digitalization of the Economy for the Indonesian Economy and Its Role During the Covid-19 Pandemic - Indah Permatasari Siregar (Enrichment : Journal of Management, 2021)
Technology has changed people's behavior a lot, one of which is economic behavior that was previously traditional and conventional to be more sophisticated by being integrated into a digital system. Economic activities such as buying and selling will never be separated from human activities. The exchange process will continue in any atmosphere and condition, such as the current condition, namely the pandemic condition due to Covid-19. Physical restrictions due to the pandemic have caused buying and selling transactions to be constrained and difficult to carry out. Economic digitization is a very effective solution for the current pandemic situation, because it can reduce physical encounters between sellers and buyers. Through this research, The author observes the impact of economic digitization on economic growth in Indonesia, especially during the COVID-19 pandemic by using descriptive qualitative research methods. The descriptive qualitative research method uses various kinds of literature such as national and international journals and trusted websites as a source of study. The results that the authors get from this study are that the pandemic has a positive impact on the development of the digital economy, because it is able to accelerate the introduction and acceptance of the use of technology in shopping or other economic activities for daily use by the community. This can be seen from the increase in electronic money transactions from 2019 to 2020 as much as Rp. 145.2 trillion to Rp. 204.9 trillion, which increased by 41.2%.